KARAKTERISTIK TUPAI DALAM BENTUK KARYA KERAMIK - ADI SAPUTRA, Drs. Suib Awrus, M.Pd., Dra. Jupriani, M.Sn (Universitas Negeri Padang, 2018)
The purpose of creation of the work these days is creating characteristic squirrel in the form of ceramic works are used as media Messenger messages on world politics, especially the problem of corruption. The theories of the creation of the artwork is a squirrel, character figures, corruption, and greed.The method of creation sof works of art, using five stages namely the preparation, elaboration, synthesis, realization of the concept, the final settlement. ceramic works exhibition. In the creation of the work, using materials with the techniques of pinching clay (kenjutsu) and uses the original color after combustion are coated with clear dof and painterly paint using a brush.Nine works made represents the themes that were raised tells the story of humans who have behavior resembles a squirrel has nine properties of the title as follows: laugh in wealth, the fruit of other people, a high position, the power in the cleverness, as smart as pasndainya jump caught also, scholars squirrels, go up, go down and enjoy a meal, each of which has meaningKeywords: ceramics, squirrels and corruption